Pengaruh Inflasi, Tingkat Bunga, Emas Dunia, dan Utang Luar Negeri Terhadap Nilai Tukar Rupiah - Ihsanul Waldi; Syamsul Amar (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2020)
This study aims to look at the effect of macroeconomic variables on the rupiah exchange rate, which in this study involves variables from internal and external factors. The independent variables used are inflation, interest rates, gold prices and foreign debt, and the dependent variable is the exchange rate. This study uses time series data in the country of Indonesia with a span of quarter 1 in 2009 to 4 in 2018. The research model uses multiple linear regression with the Ordinary Least Square (OLS) method. The results showed that inflation and interest rates did not significantly influence the rupiah exchange rate. However, the price of gold and foreign debt have a significant effect on the rupiah exchange rate.